Determinants of Economic Growth in Somalia: ARDL Model - Aden Mohamed, Abdisalan; Shire Mohamud, Salad (International Journal of Scientific Research and Management (IJSRM), 2023)
Using an autoregressive distributed lag model (ARDL) and error correction technique, this paper investigates the short- and long-run relationships between exports, imports, and FDI on economic growth in Somalia. Secondary data was collected from the SESRIC website. The study spans the years 1995 to 2020. The result of the study revealed short- and long-term relationships between the variables. While FDI and exports have a negative long-term relationship with economic growth, imports have a positive long-term relationship. It also shows that FDI has a negative, short-run insignificant relationship with economic growth, whereas imports and exports have a significant, short-run relationship. Diagnostic tests were applied, and the results demonstrate that the model's validity for Somalia's economic growth is characterized by normality, the absence of serial correlation, and heteroscedasticity